2021
DOI: 10.26803/ijlter.20.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Distance Learning amid the COVID-19 Pandemic in the UAE: High School Students’ Perspectives

Abstract: In light of the COVID-19 pandemic that has resulted in several countries being locked down, there has been a paradigm shift in terms of learning worldwide. As a result, educational institutions in the United Arab Emirates (UAE) have acted swiftly and shifted from face-to-face education to distance learning. Thus, this study investigated high school students’ perspectives on the distance learning of mathematics. The research employed a quantitative method using a developed and validated online survey. The conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Characteristic approaches of online learning also helped increase understanding (Nurliani et al, 2021;Poláková & Klímová, 2021), such as the use of videos (e.g., Rusmansyah et al, 2021) and flipped feedback (e.g., Education Scotland, 2021). In a study of Maths students in the United Arab Emirates, Almarashdi and Jarrah (2021) found that students were focused more on developing their understanding of concepts, rather than on memorising answers for tests during remote online learning.…”
Section: Cognitive Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic approaches of online learning also helped increase understanding (Nurliani et al, 2021;Poláková & Klímová, 2021), such as the use of videos (e.g., Rusmansyah et al, 2021) and flipped feedback (e.g., Education Scotland, 2021). In a study of Maths students in the United Arab Emirates, Almarashdi and Jarrah (2021) found that students were focused more on developing their understanding of concepts, rather than on memorising answers for tests during remote online learning.…”
Section: Cognitive Engagementmentioning
confidence: 99%
“…A significant number of studies mentioned that students longed for social interaction and that their social needs were not met during the pandemic (e.g., Almarashdi & Jarrah, 2021;Jayathirtha et al, 2020). One study found that support for social engagement was critical (Yates et al, 2021) and suggested that some students might attend online classes just to see their classmates (Easterly et al, 2021).…”
Section: Social Presence To Support Social Engagementmentioning
confidence: 99%
“…Secara umumnya, terdapat pelbagai dapatan yang ditunjukkan daripada kajian-kajian lepas. Antaranya, kajian lepas menunjukkan kesediaan pelajar adalah melebihi purata (Chung, Subramaniam & Dass, 2020) (Almarashdi & Jarrah, 2021). Malah, pelajar juga tidak begitu biasa untuk menggunakan perisian spesifik Matematik dalam pembelajaran (Golding, 2021).…”
Section: Kesediaan Pelajar Terhadap Pentaksiran Matematik Dalam Talia...unclassified
“…However, some students may find online learning difficult for specific subjects and courses. For example, a recent study in high school students from Grades 9–12 from Al Ain in the UAE reported that 76.7% felt that online learning was unsuitable to learn mathematics and that 78.3% would not choose mathematics distance learning if they had the choice (Almarashdi & Jarrah, 2021 ).…”
Section: Introductionmentioning
confidence: 99%